Franz I - Axmann, Joseph 1793-1873 (engraver):::Creator::::::::::::; Schiavone, Natale, 1777-1858 (artist):::Contributor:::::::::::: (Im Verlage der Franz Härter'schen Buchhandlung)
Engraving of Franz I, Emperor of Austria